Cloning of a novel signaling molecule, AMSH-2, that potentiates transforming growth factor β signaling - Pandey Akhilesh; Moustakas Aristidis; Schiemann William P; Nakajima Daisuke; Kratchmarova Irina; Ibarrola Nieves; Mann Matthias (BMC Cell Biology, 2004)
Abstract Background Transforming growth factor-βs (TGF-βs), bone morphogenetic proteins (BMPs) and activins are important regulators of developmental cell growth and differentiation. Signaling by these factors is mediated chiefly by the Smad family of latent transcription factors. Results There are a large number of uncharacterized cDNA clones that code for novel proteins with homology to known signaling molecules. We have identified a novel molecule from the HUGE database that is related to a previously known molecule, AMSH (associated molecule with the SH3 domain of STAM), an adapter shown to be involved in BMP signaling. Both of these molecules contain a coiled-coil domain located within the amino-terminus region and a JAB (Domain in Jun kinase activation domain binding protein and proteasomal subunits) domain at the carboxy-terminus. We show that this novel molecule, which we have designated AMSH-2, is widely expressed and its overexpression potentiates activation of TGF-β-dependent promoters. Coimmunoprecipitation studies indicated that Smad7 and Smad2, but not Smad3 or 4, interact with AMSH-2. We show that overexpression of AMSH-2 decreases the inhibitory effect of Smad7 on TGF-β signaling. Finally, we demonstrate that knocking down AMSH-2 expression by RNA interference decreases the activation of 3TP-lux reporter in response to TGF-β. Conclusions This report implicates AMSH and AMSH-2 as a novel family of molecules that positively regulate the TGF-β signaling pathway. Our results suggest that this effect could be partially explained by AMSH-2 mediated decrease of the action of Smad7 on TGF-β signaling pathway.